Partial checklist of Ants (Hymenoptera: Formicidae) in selected localities in and around Achalpur, District Amravati, Maharashtra, India - Ahsan, Mohammad Misbahul (International Journal of Scientific Research in Biological Sciences, 2022)
Ants are highly intelligent, social and ecologically important insects. They are known for their valuable contributions in ecosystems and found in all possible habitats. The present study deals with the checklist of ant species in and around Achalpur, Amravati district, Maharashtra, India. This work was carried out from June 2021 to December 2021 for total six months. Ants were sampled randomly by using different collection methods like all-out search method, hand collection method and species were identified with the help of standard taxonomic literature. During this study a total 09 species of ants were recorded under 07 genera belonging to 03 subfamilies. Myrmicinae (five species) was found to be a most abundant subfamily in terms of species followed by Formicinae (three species) and Dolichoderinae (one species).